A Case of Malignant Right Coronary Artery: Frequent Angina in Young Person - Purwowiyoto, Sidhi Laksono; Surya, Steven Philip (Folia Medica Indonesiana, 2021)
Highlight: • A young adult has activity-triggered atypical chest pain and diagnosed malignant RCA. • Congenital anomalies needed to be aware by cardiologists to help clinical practice. • Planning a treatment about management of the CAAs condition should be undertaken by the inter-specialist team. Abstract: We presented a case a young adult with activity-triggered atypical chest pain and diagnosed with anomalous origin of right coronary artery (RCA) from the left coronary sinus with an interarterial course between the aorta and the main pulmonary artery that was detected by CT coronary angiography. This anomaly has been called malignant RCA. Coronary artery anomaly is a congenital condition. Most of the cases remain asymptomatic. This condition is also one of the most causes of sudden cardiac death, because the coronary artery examination is not regularly done. Nevertheless, during high intensity activity, it could be symptomatic and might be lethal. Diagnosing coronary artery anomalies might be tricky and cardiologists must be aware of this. The CAAs condition is a rare situation. The CAAs condition is associated with sudden death, especially intense physical activity. There was no rigid guideline for the management of the CAAs condition, so that planning a treatment in the inter-specialist team should be done.